OPTIMIZATION OF ENZYMATIC HYDROLYSIS OF RAMIE DECORTICATION WASTE-BASED CELLULOSE USING RESPONSE SURFACE METHODOLOGY - Laeli Kurniasari; Suwardiyono Suwardiyono; Renan Subantoro; Indah Hartati (Fakultas Teknik Universitas Wahid Hasyim, 2017)
Ramie is a herbaceous species which is usually used to produce fibre. The decortication process of ramie will leave the waste that still contain high cellulose. The high cellulose content of ramie decortication waste is a potential raw material for producing bioethanol.Cellulose conversion into bioethanol need four consecutive process e.g. pretreatment, hydrolysis, fermentation and purification. This research is combining microwave heating in the alkaline pretreatment toward the ramie decortication waste and followed by investigating the optimization of enzymatic hydrolysis of ramie decortication waste-based cellulose. The cellulase used in the hydrolysis process was isolated from cow rumen fluids. Response Surface Methodology was used for the optimization of hydrolysis process. A 23Central Composite Design (CCD) was used to develop statistical model and analyze the effect of each variables, which are hydrolysis time (36-60 hr), solid liquid rasio (2-4%) and temperature (35-450C). The optimum condition obtained for the hydrolysis of RDW was temperature 410C, solid liquid rasio 3,4% and time 48,9 hr with glucose content was 3,51 mg/g. Keywords:cow rumen, enzymatic hydrolysis, ramie decortication waste